A comparative analysis of pre-service teachers’ readiness for AI integration - Margarida Lucas; Pedro Bem-haja; Yidi Zhang; Carmen Llorente-Cejudo; Antonio Palacios-Rodríguez (Computers and Education: Artificial Intelligence)
Artificial Intelligence (AI) is impacting the way we teach and learn. However, there are still substantial barriers to the integration of AI in educational settings, as teachers often lack the necessary competences to understand and use AI for pedagogical purposes. Therefore, in the early stages of teacher preparation, it is essential to assess the readiness of pre-service teachers for this transition in different initial teacher education (ITE) contexts. This study aims to investigate the readiness of pre-service teachers in Portugal and Spain to integrate AI into future teaching practices. To this end, a study was conducted with 203 pre-service teachers from both countries that compared results regarding different dimensions: trust in AI, knowledge of AI, digital competence and ITE training for AI. The study further examined the relations between these dimensions. The results showed no significant differences between the two countries for trust in AI, knowledge of AI and digital competence. Significant differences were observed for ITE training for AI, with the Spanish sample scoring higher. However, these differences were limited to the distinction between disagreement and neutrality, suggesting that pre-service teachers in both countries are not fully ready to integrate AI into their future teaching practices. The results also showed that ITE training for AI had almost no significant influence on both samples’ trust in AI, knowledge of AI and digital competence, suggesting that ITE in both countries are not integrating AI into their programmes. The study identifies aspects within ITE programmes that need to be reviewed to adequately qualify future teachers for AI readiness and provides practitioners, ITE providers and policy makers with insights to consider when updating ITE programmes.